Analisis Faktor Penyebab Residivisme dan Efektivitas Program Pembinaan di Lembaga Pemasyarakatan Kelas IIB Singaraja, Bali - Ni Luh Ayu Diah Wulandari Sudiawan; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku; Si Ngurah Ardhya; I Komang Wiranata (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The rate of recidivism in the Singaraja Class IIB Correctional Institution (Lapas) is a serious challenge to the effectiveness of the correctional system in realizing restorative justice and social reintegration as mandated by Law Number 22 of 2022. This juridical-empirical research with a qualitative descriptive analytical approach aims to identify the factors that cause recidivism and evaluate the effectiveness of the coaching program that runs in Singaraja Prison. The results of the study show that recidivism in the North Bali region is driven by the accumulation of internal and external factors, with economic constraints, administrative requirements for SKCK in the formal work sector, social stigmatization in communal culture, and high levels of substance dependence in narcotics cases as the main triggers. From the institutional aspect, personality development programs based on Hindu local wisdom and independence development in the form of practical skills training have been running optimally in prisons. However, the effectiveness of the coaching decreased significantly after the inmates were released due to the absence of an integrated post-release care program. This failure to adapt requires strategic collaboration between prisons, local governments, and indigenous peoples to break the chain of repeated crime through labor distribution and inclusive social recovery.